2020
DOI: 10.1103/physrevlett.125.071802
|View full text |Cite
|
Sign up to set email alerts
|

Global Fit to Modified Neutrino Couplings and the Cabibbo-Angle Anomaly

Abstract: Recently, discrepancies of up to 4σ between the different determinations of the Cabibbo angle were observed. In this context, we point out that this "Cabibbo-angle anomaly" can be explained by lepton flavor universality violating new physics in the neutrino sector. However, modified neutrino couplings to standard model gauge bosons also affect many other observables sensitive to lepton flavor universality violation, which have to be taken into account in order to assess the viability of this explanation. There… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
104
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 121 publications
(106 citation statements)
references
References 113 publications
2
104
0
Order By: Relevance
“…Notice that the CP invariant is suppressed by the sixth power of θ, hence the importance of ensuring large mixing and the reason to consider low scale seesaw realizations in this context that decouple its size from the smallness of neutrino masses. Nevertheless, constraints from precision electroweak and flavour observables exist [72][73][74][75][76][77][78][79][80] on the combination θθ † . Indeed, θθ † represents the coefficient of the only dimension 6 operator obtained at tree level 3 when integrating out the heavy neutrino degrees of freedom [82].…”
Section: Jhep10(2020)063mentioning
confidence: 99%
See 1 more Smart Citation
“…Notice that the CP invariant is suppressed by the sixth power of θ, hence the importance of ensuring large mixing and the reason to consider low scale seesaw realizations in this context that decouple its size from the smallness of neutrino masses. Nevertheless, constraints from precision electroweak and flavour observables exist [72][73][74][75][76][77][78][79][80] on the combination θθ † . Indeed, θθ † represents the coefficient of the only dimension 6 operator obtained at tree level 3 when integrating out the heavy neutrino degrees of freedom [82].…”
Section: Jhep10(2020)063mentioning
confidence: 99%
“…This choice for m dα implies that the neutrino Yukawa couplings to the second and third heavy states have the same magnitude. Additionally, it makes the coupling to the muon to vanish, for which the bounds on θθ † are the most stringent [78][79][80]. Therefore, the matrix m D now depends on a single parameter, m dτ .…”
Section: Jhep10(2020)063mentioning
confidence: 99%
“…However, low-energy precision experiments have accumulated intriguing hints for the violation of lepton flavor universality within recent years [see, e.g., Refs. [8][9][10][11][12][13][14][15][16][17][18] for b → cτν, b → sl þ l − , and RðV us Þ]. In particular, the Brookhaven measurement of the anomalous magnetic moment of the muon ðg − 2Þ μ [19] shows a tension of about 3.7σ with the SM prediction [for the electron, an analogous 2.5σ difference (but with opposite sign) between the SM prediction [44,45] based on the Cs measurement of the fine-structure constant α [46] and the direct measurement of ðg − 2Þ e [47] has emerged [48,49] ].…”
mentioning
confidence: 99%
“…Here, there is the longstanding discrepancy in ðg − 2Þ μ of about 3.7σ and a recently emerging deviation in the electron case of 2.5σ, interestingly, with the opposite sign [67][68][69][70][71][72][73]. Furthermore, it has been shown that LFU violating neutrino interactions with SM gauge bosons give an excellent fit of electroweak data, including LFU tests [74].…”
mentioning
confidence: 82%
“…In this context, it seems natural to consider the discrepancies between the different determinations of V ud (or, equivalently, V us under the assumption of CKM unitarity), in particular the direct determination from β decays, not as a sign of right-handed currents or as a violation of CKM unitarity, but rather as a sign of LFUV [74]. In fact, the most precise determination of V ud from K → μν involves muons, while β decays can only have electrons in the final states.…”
mentioning
confidence: 99%